Do we pay for maxillary protraction? Evaluation of the effects of Alt-RAMEC protocol and face mask treatment on root development - YILMAZ, HANİFE NURAY (SPRINGER HEIDELBERG, 2022)
Objectives To evaluate root development of pediatric patients treated with Alt-RAMEC + Face mask therapy. Material and methods The 19 subjects (9 girls, 10 boys; mean age: 8.6 +/- 1.1 years) treated with Alt-RAMEC and a Petit-type face mask were included to the study. The cone-beam tomography (CBCT) records of these patients were used to quantify the root length. The root length measurements of 456 permanent teeth (maxillary-mandibular incisors, canines, premolars, and first molars) were performed at the beginning of the treatment (T0), after the Alt-RAMEC protocol (T1), and at the end of the face mask treatment (T2) using Planmeca Romexis software. Results Tooth length values increased significantly in the maxillary teeth except the central incisors, left lateral incisor, the palatal root of the right first molar, and distal and palatinal roots of the left first molar (p < 0.05). Mandibular teeth also showed significant increase in the root length except mandibular central incisors and the distal root of left first molar (p < 0.05). The change in tooth lengths from T0 to T1 showed positive delta values. The comparison of the change in tooth lengths after the Alt-RAMEC protocol and after the face mask therapy showed that increment T2-T1 was statistically significantly higher compared with increment T1-T0 (p < 0.05). Conclusions Alt-RAMEC + Face mask therapy seem not to inhibit root development of maxillary and mandibular teeth in the mixed dentition.
Keywords: Alt-RAMEC; Face mask; Root resorption; Root development; Side effect; BEAM COMPUTED-TOMOGRAPHY; PALATAL EXPANSION; RESORPTION; MOLAR; ACCURACY; THERAPY; FORCE